Níveis de infecção de Babesia bovis, B. bigemina e Anaplasma marginale em búfalos criados no estado de São Paulo - Néo, Thalita Athiê (2016)
Bovine babesiosis and anaplasmosis are distinct diseases, which constitute the syndrome called tick fever, characterized by infection of red blood cells. Its distribution in herds causes the reduction in productivity and high economic losses to livestock worldwide. Anaplasma marginale, Babesia bovis, and Babesia bigemina are the predominant species in Brazil. Rhipicephalus (Boophilus) microplus is the biological vector of babesiosis and anaplasmosis may be transmitted by ticks, hematophagous flies, and fomites. It is known that the water buffalo can become infected with Babesia and Anaplasma, but little is known the extent of the infection and how it affects the health of these animals. Thus, the present study aimed to determine the frequency and the level of infection by B. bovis, B. bigemina and A. marginale in 108 water buffalo (50 calves and 58 adult females), naturally infested with the tick R. (B). microplus raised in farms located in areas of endemic stability in São Paulo state. From each animal, a blood sample from the jugular vein was taken for DNA extraction and packed cell volume (PCV) determination. Samples from auricular vessels were taken for blood smears. The body temperature was measured with a mercury thermometer column. Electrochemical impedance spectroscopy technique was used to differentiate the serum of uninfected animals from the serum of animals infected with B. bovis. To this end, antigens derived from culture were immobilized on gold electrodes (150 nm thick) to give a biosensor device using the compound [Fe (CN) 6] 3- / 4-proof redox. The peripheral blood smears were stained with May-Grunwald-Giemsa for research of hemoparasites by optical microscopy. DNA extractions were performed using the Easy DNA TM Kit (Invitrogen). DNA amplification protocols were tested with primers specific to B. bigemina, B. bovis, and A. marginale using nested PCR (nPCR) and quantitative real-time PCR (qPCR). qPCR was used to estimate the number of copies of the gene cytochrome b (mt-cytB) of both babesias and Anaplasma msp 1b gene in all samples. Merozoites of B. bigemina were seen in blood smears of three calves from the Alambari herd (all less than 0.1 of parasitemia). Molecular techniques, nPCR, and qPCR, were more sensitive in the detection of parasites that direct examination of the blood smears and the frequencies of infection were 20:37% and 100% for B. bovis and 59.26% and 100% to B. bigemina, respectively. CN of the mt-cytB gene of B. bovis and B. bigemina showed significant effects (p <0.05) of herd age, species, and their interaction. The CN values were higher (p≤0.05) for B. bovis (2.81 ± 0:07) when compared to B. bigemina (2.61 ± 12:07) and A. marginale (0:57 ± 0:07). These data suggest a high frequency of infection by B. bovis and B. bigemina in the population of water buffalo studied. Preliminary testing of diagnosing infection with B. bovis device showed changes in the impedance in the system used and clearly demonstrated that the biosensor can detect infected animals, which can be exploited for rapid detection of B. bovis infections and also extended for the test to other parasites.